Michael Vey: Storm of Lightning - Book 5 - Evans, Richard Paul (New York : Mercury Ink/Simon Pulse, 2015)
"Michael and the rest of the Electroclan are facing their greatest crisis yet. The resistance movement has been compromised. The safe house has been destroyed. The voice is in hiding, and they have no idea if their families are alive... or dead. What they do know is that the Elgen won't stop until they've destroyed the Electroclan"--Front jacket flap.
Keywords: Teenagers -- Juvenile fiction; Friendship -- Juvenile fiction; Missing persons -- Juvenile fiction; Electricity -- Juvenile fiction; Tourette syndrome in adolescence -- Juvenile fiction; Teenagers -- Fiction; Friendship -- Fiction; Missing persons -- Fiction; Electricity -- Fiction; Tourette syndrome -- Fiction; Science fiction; Science fiction